2022
DOI: 10.3389/fendo.2022.861443
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Comorbid Diabetes on Clinical Characteristics of COVID-19 Patients Infected by the Wild-Type or Delta Variant of SARS-CoV-2

Abstract: BackgroundDiabetes is one of the most common comorbidities in COVID-19 patients that pertains to disease severity, but the causal mechanism regarding its negative impact on COVID-19 outcome has yet been uncovered.MethodsWe retrospectively analyzed 459 COVID-19 patients admitted in early 2020 and 336 COVID-19 patients admitted in August 2021, with their demographic information, medical history, vaccination status (if applied), and laboratory data reported.ResultsAmong COVID-19 patients, compared to the non-diab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…Specifically for influenza, DM is associated with a higher frequency and more severe clinical course, similarly, also mycobacterial infections may be more frequent and more severe in individuals with DM 27. Diabetes is also a known risk factor for SARS-CoV-2 infection as well as worse COVID-19-related mortality 7 28–34. In a study from England, obesity itself was associated with higher COVID-19-related hospitalization or death even within the vaccinated cohort after adjustment for the presence of DM 31…”
Section: Discussionmentioning
confidence: 99%
“…Specifically for influenza, DM is associated with a higher frequency and more severe clinical course, similarly, also mycobacterial infections may be more frequent and more severe in individuals with DM 27. Diabetes is also a known risk factor for SARS-CoV-2 infection as well as worse COVID-19-related mortality 7 28–34. In a study from England, obesity itself was associated with higher COVID-19-related hospitalization or death even within the vaccinated cohort after adjustment for the presence of DM 31…”
Section: Discussionmentioning
confidence: 99%
“…Viruses and host immunity may also be correlated, indicating a certain evolutionary direction. 13 , 14 , 15 , 16 It has been reported that approximately 10% of hospitalized patients are susceptible to COVID‐19, which is associated with prolonged hospital stay and increased risk of postoperative complications, particularly in elderly patients with diabetes, chronic obstructive pulmonary disease, or other frail or immune abnormalities. The increase in COVID‐19 cases will bring additional challenges and increase global medical burden.…”
Section: Pandemic Symptoms and Vaccines Of The Covid‐19mentioning
confidence: 99%
“…COVID-19, which infects patients with comorbid diabetes mellitus will worsen the patient's condition (Zhang et al, 2022). In a study, it was stated that in patients infected with COVID-19 and having type 2 diabetes mellitus, viral shedding was prolonged, while the duration of viral shedding is positively associated with the level of severity (Arfijanto et al, 2023).…”
Section: Introductionmentioning
confidence: 99%